(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
INTRODUCTION: Intestinal obstruction is frequently encountered in differential diagnosis of patients presenting with a acute abdomen. Even with an early diagnosis bowel obstruction still represent some of the most difficult problems that surgeons face with regard to optimal timing of therapy and appropriate management in different type of bowel obstruction. AIMS AND OBJECTIVES: To study the various modes of presentation, importance of early diagnosis and management of patients , the incidence of different complications during treatment and their management in tertiary care centre of urban population. MATERIALS AND METHODS: This study was conducted for a period of 2 years with patients admitted from 01/ 07/ 2017 up to 30/06/ 2019 with a sample size of 50 patients in L.G. hospital, Ahmedabad .Present study was prospective, observational, cross-sectional study. OBSERVATIONS AND DISCUSSION: Out of 50 patients, 70% were males and 30% were females, more commonly in young patients (11-20 yrs age). Most common presenting cause of intestinal obstruction is subacute intestinal obstruction which is 20 % and these cases were managed conservatively. Conservative approach was helpful in 38% of cases due to their early presentation and subacute type of obstruction most commonly. Primarily operative approach after initial resuscitation were 32% of total cases with indications like acute presentation with tenderness, abnormal peristalsis like absent or hyperperistalsis, fever, irreducible or palpable lump, ultrasonography finding of peritonitis etc. Most common complication encountered was wound infection 35% of operated cases. Mortality was 4 % occurrence in present study. CONCLUSION: Of the 50 cases of intestinal obstruction in our study adhesions and bands are the common cause to produce intestinal obstruction. Koch’s abdomen is also increasingly encountered in etiology of intestinal obstruction as stricture and it is related to poor socioeconomic status of study population in present study. Hernia related obstruction were higher in early twentieth century but decreasing nowadays. It suggests that planned hernia repair can avoid this complication. With better understanding of etiology due to advanced diagnostic ailments mortality rate is decreasing.